2021
DOI: 10.1186/s12935-021-02264-5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ferroptosis in urologic malignancies

Abstract: Ferroptosis, an iron-dependent form of non-apoptotic cell death, is believed to strongly contribute to the pathogenesis of multiple cancers. Recently, the positive association between ferroptosis and urologic malignancies has drawn considerable attention, while a comprehensive review focused on this issue is absent. Based on this review, ferroptosis has been implicated in the development and therapeutic responses of prostate cancer, kidney cancer, and bladder cancer. Mechanistically, a large number of biomolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 126 publications
(188 reference statements)
0
19
0
1
Order By: Relevance
“…This combined treatment supports the development of novel treatment strategies that target VHL-deficient RCC and chemoresistant ovarian cancers (97,98). By utilizing hypoxia-inducible lipid droplet associated protein, the VHL/HIF-2α pathway may induce ferroptosis by upregulating lipid peroxidation levels (99). The Warburg effect, demonstrated by increased glycolytic intermediate labeling, decreased pyruvate dehydrogenase flow and decreased tricarboxylic acid cycle labeling, has been observed in various primary ccRCC cases (100).…”
Section: Ddr Genes and Precision Treatment Of Renal Cancermentioning
confidence: 54%
“…This combined treatment supports the development of novel treatment strategies that target VHL-deficient RCC and chemoresistant ovarian cancers (97,98). By utilizing hypoxia-inducible lipid droplet associated protein, the VHL/HIF-2α pathway may induce ferroptosis by upregulating lipid peroxidation levels (99). The Warburg effect, demonstrated by increased glycolytic intermediate labeling, decreased pyruvate dehydrogenase flow and decreased tricarboxylic acid cycle labeling, has been observed in various primary ccRCC cases (100).…”
Section: Ddr Genes and Precision Treatment Of Renal Cancermentioning
confidence: 54%
“…Meanwhile, the top 20 KEGG pathways with the condition of a p -value under 0.006 are shown in the Sankey diagram ( Figure 2 D). We found that some KEGG pathways were highly associated with ferroptosis, such as pathways in cancer [ 33 ], PI3K-Akt signaling pathway [ 34 ], lipid and atherosclerosis [ 35 ] and p53 signaling pathway [ 36 ] ( Figure 2 E). Thus, we speculated that ferroptosis might be involved in the anti-inflammatory process of catechin.…”
Section: Resultsmentioning
confidence: 99%
“…In the future, the incidence of BC will increase globally due to increased exposure to BC carcinogens and global aging(26). Ferroptosis is a newly discovered form of iron-dependent non-apoptotic cell death, which is closely relevant to the pathogenesis of various cancers (27). A Previous study has demonstrated that the natural product baicalin can inhibit cancer progression by inducing ferritin heavy chain 1-dependent (FTH-1) ferroptosis(28).…”
Section: Discussionmentioning
confidence: 99%